A novel approach to enhance glioblastoma multiforme treatment efficacy: non-coding RNA targeted therapy and adjuvant approaches - Meijun Liu; Yuying Wang; Xiaoli Chen; Yu Zeng; Wenqiong Huang; Jiawen Yang; Hong Dai; Lixin Cheng; Claudio Mauro; Kenneth Chat Pan Cheung (Clinical Epigenetics)
Abstract Background Glioblastoma multiforme (GBM) is a lethal brain tumor. With the current gold standard chemotherapy treatment, temozolomide (TMZ), many patients do not survive beyond one year. While the urgency of researching novel treatments is understandable, the prohibitively high costs and the prolonged duration of research and clinical trials significantly delay the availability of medical advancements to the general public. This highlights the urgent need for adjuvant therapies to enhance treatment effectiveness. Main body: Recent research has suggested the potential of repurposing FDA-approved drugs such as temozolomide (TMZ), disulfiram (DSF), and aspirin for the treatment of glioblastoma, with encouraging evidence particularly for DSF and aspirin. Additionally, compounds like histone deacetylase inhibitors (e.g., vorinostat) are being investigated for their impact on non-coding RNA (ncRNA) modulation, including microRNAs (miRNAs) and long non-coding RNAs (lncRNAs). Combining traditional therapies with ncRNA modulation has shown potential in enhancing therapeutic efficacy and targeting specificity. NcRNAs play a crucial role in regulating gene expression and have been implicated in tumor growth, invasion, and treatment resistance. Recent discoveries, such as cuproptosis, offer new insights into tumor cell death mechanisms. Conclusion This review focuses on how these molecular insights can serve as novel therapeutic targets and how drug adjuvant therapy may improve GBM treatment strategies. It focuses on how the integration of ncRNA modulation with conventional therapies and the combination strategy of enhancing efficacy of drugs can enhance treatment efficacy and pave the way for innovative approaches in managing GBM. In short, we will explore how non-coding RNAs (ncRNAs) might serve as promising targets and how repurposing TMZ, DSF, and aspirin could help enhance the efficacy of GBM treatment. Graphical abstract